Adaptation and ecological speciation in seasonally varying environments at high latitudes: Drosophila virilis group. Issue 1 (31st December 2022) - Hoikkala, Anneli; Poikela, Noora
ABSTRACT: Living in high latitudes and altitudes sets specific requirements on species' ability to forecast seasonal changes and to respond to them in an appropriate way. Adaptation into diverse environmental conditions can also lead to ecological speciation through habitat isolation or by inducing changes in traits that influence assortative mating. In this review, we explain how the unique time-measuring systems of Drosophila virilis group species have enabled the species to occupy high latitudes and how the traits involved in species reproduction and survival exhibit strong linkage with latitudinally varying photoperiodic and climatic conditions. We also describe variation in reproductive barriers between the populations of two species with overlapping distributions and show how local adaptation and the reinforcement of prezygotic barriers have created partial reproductive isolation between conspecific populations. Finally, we consider the role of species-specific chromosomal inversions and the X chromosome in the development of reproductive barriers between diverging lineages.